INTELLECTUAL CAPITAL, PROFIT SHARING RATIO, DAN CORPORATE GOVERNANCE PADA BANK UMUM SYARIAH DI INDONESIA - Tri Wahyudi (FEB Universitas Sultan Ageng Tirtayasa, 2019)
This research is meant to analyze the influence of intellectual capital to the profit sharing ratio (PSR) of Syariah Commercial Banks with corporate governance as the intervening variable. The population is Syariah Commercial Banks which are listed in Bank Indonesia in 2011-2016 periods which is done by using the financial statement data which has been obtained by using purposive sampling and based on the determined criteria, so 57 (fifty seven) samples which have met the criteria. The analysis technique has been done by using multiple linear regressions analysis and path analysis. Based on the result of multiple linear regressions analysis and path analysis with its significance rate is 5% so that the result of this research shows that: 1) intellectual capital has not influence to the profit sharing ratio (PSR), 2) intellectual capital has influence to the profit sharing ratio (PSR) with corporate governance as intervening variable.